"That makes all the difference": Aboriginal and Torres Strait Islander health‐seeking on social media. (26th June 2020) - Carlson, Bronwyn; Frazer, Ryan; Farrelly, Terri
Abstract: Issue Addressed: Little is known about the complex relationships between Australian Indigenous people's use of social media and "health‐seeking" – seeking help for issues related to health and well‐being. This paper has emerged from a broader sociological research project focusing on the help‐seeking and help‐giving practices of Aboriginal and Torres Strait Islander people on social media, specifically aiming to unlock its potential to create vital and creative connections between help‐seekers and help‐givers. Methods: Semi‐structured interviews were conducted with 52 Indigenous Facebook users from five sites across Australia. Results: The use of grounded theory and Indigenous‐centred methodologies for analysis showed clearly that users draw on the connections made possible through Facebook to health‐seek. We identify five primary health‐seeking strategies that differ in form, purpose and directness: soliciting health‐related information, gaining emotional support, producing social health‐seeking collectives, engaging in motivational and "eudaimonic" content, and connecting with formal health sources. Conclusion: While far from being a panacea to health disparities, these findings show that Facebook does provide unique opportunities for many Indigenous help‐seekers and help‐givers in times of need. So What?: Social media offers pathways for health‐seeking both beyond and outside the dominant western biomedical models of public health promotion. These already‐existing pathways should be considered by people working on social media public health promotion campaigns for Aboriginal and Torres Strait Islander people.